The impact of attention-deficit / hyperactive disorder on interpersonal relationships and self-esteem - Oshodin, Uwafiokun Aituayuwa (My University, 2016)
Background: ADHD is a neurodevelopmental disorder affecting 3 – 7% of school age children. The core symptoms of ADHD, hyperactivity, impulsiveness and inattentiveness often cause problems in many aspects of life, including interpersonal relationships. The problems associated with the disorder may also lead to poor self-esteem. Objective: To assess the impact of attention-deficit/hyperactivity disorder (ADHD) symptoms on interpersonal skills and self-esteem in a non-referred sample of primary school children meeting criteria for a diagnosis of ADHD. Method: Eighty-two children with ADHD (6 – 13 years) were selected using a convenient sample screened from primary schools in the Limpopo Province and were compared to 82 children without significant ADHD symptoms, who match the ADHD children on age and gender. The children were screened and diagnosed using the Disruptive Behaviour Disorders rating scale (DBD). They were assessed on two instruments: The PHSF (Personal, Home, Self and Formal) relations questionnaire was used for the measurement of interpersonal relationship while self-esteem was measured using the self-concept inventory of the Beck Self-Concept Inventory for youths [BSCI-Y]. The scores obtained on the two scales were compared for significant differences between the ADHD group and the non-ADHD comparisons as a possible function of gender. Results: Children with ADHD scored significantly higher (p < 0.001) on the scale that measured problems with interpersonal relationships (PHSF) than the non-ADHD comparison group. There was no effect of gender. The measurement instrument for self esteem (BSCI-Y) indicated that the children with ADHD had higher self-esteem than their non-ADHD comparisons (p < 0.001). Gender did not affect the difference between the groups. Conclusion: The findings indicated that children, who are inattentive, impulsive and over active, which are symptoms of ADHD, will have poorer interpersonal relationships than children without the disorder. Findings from the result of the measurement of self-esteem indicated that children with ADHD could have higher self-esteem than children without ADHD. The latter is in contrast with findings of most studies and may be ascribed to an unrealistic self-concept because of the young age of the participants or possible cultural factors.
Thesis (M.A. (Psychology)) -- University of Limpopo, 2016.
Keywords: Attention-Deficit/Hyperactivity Disorder (ADHD); Self-esteem; Attention-decifit disordered children; Attention-deficit disorderd children -- Education; Hyperactive children; Self-esteem in children